Pinus elliottii natural regeneration in forest gaps: seven years population dynamics - Rebottaro, Silvia L.; Cabrelli, Daniel A. (Instituto de Ecología, A.C., 2016)
We evaluated the dynamics of Pinus elliottii (Engelm.) natural regeneration in silvicultural gaps after strip clearcutting. Two orientations: EW and NS, and three size of gaps: ratio strip width/hight tree of 0,5; 0,8 y 1,1 were analyzed. Density, recruitment, mortality, diameter and height of plants were monitored during seven years. The light environment was characterized using hemispherical photographs, and calculating relative radiation direct (Rd), indirect (Ri) and total (Rt). In general, plants density was enough to begin a productive cycle (2,7-8,1 plants m-2). The only critical condition was generated in strip 0,5 with NS orientation (radiatión < 55%), where density was 0,2-0,3 plants m-2. Whatever of the orientation, the strips 0,8 y 1,1 have good plants establishment, and relative higher than 65%. The recruitment was registered mainly during winter and spring. The mortality had more impact during spring-summer. More favorable condition for the growth was found in 1,1 strip with EW orientation, where Rt was 73%. Nine years after openning canopy, the analysis of tallest plants demonstrated differences between gaps.